Radiographic and Anatomic Evaluation of Tibial Tubercle to Trochlear Groove Distance - Worden, Alicia; Kaar, Scott; Owen, Joshua; Cutuk, Adnan (The Journal of Knee Surgery, 2016)
Background A lateralized tibial tubercle is an important anatomic predictor of patellar instability and can be used as an indication for a distal realignment procedure. Currently, tibial tubercle to trochlear groove (TT-TG) distance is measured on computed tomography (CT); however, radiographs could be a safer and more efficient modality. The aim of this study is to evaluate and compare TT-TG measurements obtained using CT, anatomical dissections, and a novel radiographic technique. Furthermore, we evaluated the effects of knee flexion and tibial rotation on these measurements.Methods TT-TG distances were measured on 11 fresh cadaver specimens with CT and compared with anatomic measurements obtained from dissection in full knee extension and 90-degree flexion. Both imaging- and dissection-derived measurements were obtained in neutral, external, and internal tibial rotation. The TT-TG distance was also measured on a modified sunrise X-ray view (knee at 90 degrees).Results The TT-TG distance obtained on CT was 13.00 ± 1.05 mm and was comparable to measurements derived from anatomic dissections in extension (14.88 ± 1.10 mm) and 90 degrees (12.40 ± 1.93 mm) (p ≥ 0.05). The X-ray measurements of TT-TG distance (5.62 ± 1.16 mm) were significantly different than those measured on CT (p ≤ 0.05). TT-TG distances in neutral tibial position measured on CT and dissection were significantly different than distances measured in full external (19.79 ± 1.33 and 20.92 ± 1.15 mm, respectively) and internal tibia rotation (6.45 ± 1.00 and 10.33 ± 1.19 mm, respectively) (p ≤ 0.05).Conclusions TT-TG distance measured on CT is comparable to measurements from dissections in both full extension and 90-degree flexion. Tibial rotation has a significant effect on TT-TG measurements. Radiographic measurements did not correlate with CT and anatomic measurements.Clinical Relevance CT-derived TT-TG measurements are accurate throughout knee range of motion; however, it is important to maintain neutral lower leg rotation to not generate a false-positive or false-negative measurement. Radiographic measurement of TT-TG ration is not currently recommended.
Keywords: patellofemoral instability; TT-TG distance; computed tomography; radiographs